2015
DOI: 10.3390/molecules20011228
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activity in Different Tissues of Brassica Vegetables

Abstract: This research was conducted to evaluate glucosinolate profiles, vitamin C, total phenol, total flavonoid, and free sugar (glucose, fructose, and sucrose) content, fatty acid composition, and antioxidant activity in floret and leaf of six cauliflower and broccoli cultivars. The level of chemical constituents as well as antioxidants significantly varied among crop types, cultivars, and their different parts, in that phytochemicals such as glucosinolate were statistically higher in florets compared with leaves in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
83
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 42 publications
18
83
3
1
Order By: Relevance
“…Results obtained in this study are in agreement with fi ndings of Bhandari & Kwak [2015] and Picchi et al [2012], who reported that vitamin C content in caulifl ower ranged from 396.7 to 649.7 and from 346 to 638 mg/100 g dry mass, respectively. On the other hand, Mazzeo et al [2011] reported a higher content of ascorbic acid in raw caulifl ower -863.3 mg/100 g of dry mass.…”
Section: Vitamin Csupporting
confidence: 93%
“…Results obtained in this study are in agreement with fi ndings of Bhandari & Kwak [2015] and Picchi et al [2012], who reported that vitamin C content in caulifl ower ranged from 396.7 to 649.7 and from 346 to 638 mg/100 g dry mass, respectively. On the other hand, Mazzeo et al [2011] reported a higher content of ascorbic acid in raw caulifl ower -863.3 mg/100 g of dry mass.…”
Section: Vitamin Csupporting
confidence: 93%
“…This crop is a fresh vegetables which become Indonesian export commodities (CBSI, 2014). It is a good source of protein, thiamin, riboflavin, phosphorus and potassium, and a very good source of dietary fiber, vitamin C, vitamin K, vitamin B6, folate, *Coressponding Author: M. Simarmata; E-mail: marulak_simarmata@yahoo.com pantothenic acid and manganese (Bhandari and Kwak, 2015). This vegetable is also low in saturated fat and cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…In regard to the changes of glucosinolate contents in broccoli upon CA treatment, discrepant results were obtained in various broccoli cultivars under different storage temperatures combined with diverse O 2 and CO 2 concentrations. Hansen et al [172] investigated the changes of glucosinolates in 'Marathon' broccoli florets stored under low O 2 and high CO 2 . Results showed that the total glucosinolate content increased 42 % under air and 21 % under 0.5 % O 2 + 20 % CO 2 during 7-day storage at 10°C when compared to freshly harvested broccoli.…”
Section: Controlled Atmosphere Storagementioning
confidence: 99%
“…italica) is an economically important vegetable crop in many countries and has been highly valued by consumers due to its flavor as well as its nutritional components like minerals, vitamins, polyphenols, and other beneficial phytochemicals, particularly potent anticarcinogenic glucosinolates (GSs) [1][2][3][4]. Epidemiological studies have suggested that the consumption of broccoli could lower the risk for the development of certain forms of cancers, which have been attributed to glucosinolates and their degradation products [5,6].…”
Section: Introductionmentioning
confidence: 99%